Enhancing The Bone Formation Properties Of Chondroitin Sulphate Based Injectable Hydrogels Incorporated With Dap And Cu Nanoparticles Using Cissus Quadrangularis - Aarthi. K, Aarthi. K; Ganesh, Balagi; Eswaramoorty, Rajalakshmanan (Journal of Neonatal Surgery, 2025)
Introduction: Chondroitin sulfate (OS) IS a naturally occurring glycosaminoglycan, commonly found in connective tissues such as cartilage and bone. Chondroitin sulfate, a naturally occurring polysaccharide, is a fundamental component of the extracellular matrix in various tissues, most notably in cartilage. Cartilage, with its limited regenerative capacity, poses a significant challenge in the field of tissue engineering and regenerative medicine. Materials and Method: Chondroitin sulfate-based injectable hydrogels enriched with dapsone (DAP) and copper (Cu) nanoparticles are formulated. Cissus quadrangularis extract is integrated. The materials synergistically enhance bone formation properties, combining anti-inflammatory effects of DAP, osteogenic benefits of Cu nanoparticles, and bioactive compounds from Cissus quadrangularis for improved regenerative outcomes in orthopedic applications. Results: Presented that the hydrogel formed fast in situ after injection due to the non-covalent cross-linking, and then reinforced by the DA chemical cross linking.The study determined the percentage of cell viability between the sample and control group. In addition, mechanical property of the hydrogel under dynamic conditions was determined to mimic dynamic bone tissues. Conclusion: Chondroitin sulphate-based injectable hydrogels represent an exciting development in the field of regenerative medicine and orthopedics. They have shown promising results in bone tissue engineering, promoting bone formation and repair due to their excellent biocompatibility, biodegradability, and mimicking of the natural extracellular matrix.